Antibiotic Resistance Pattern among Bacteria causing Ventilator Associated Pneumonia in An Intensive Care Unit of Bangladesh (Bangladesh Critical Care Journal, 2016)
Background : Ventilator-associated pneumonia (VAP) is the most common type of nosocomial infection in critical care practice with high morbidity and mortality. Microorganisms responsible for VAP vary from place to place. So, identification of causative organism and knowledge of their resistance pattern is very important for empirical choice of antibiotic in managing VAP. The aim of this survey was to evaluate the quantitative cultures of endotracheal aspirates to determine the microorganisms responsible for VAP and to study their antibiotic resistance pattern.Materials and Methods: This cross sectional study was performed over a period of six month starting from November, 2015 to April, 2016 in the Intensive Care Unit (ICU) of BIRDEM General Hospital. Patients with a clinical and radiological diagnosis of VAP were included in this study.Result: A total of 51 patients with a clinical diagnosis of VAP were included in this study. Growth was obtained in100% of the samples yielding 88 organisms. Gram-negative organisms were the mostly isolated organism (76.13%), followed by fungi (17.04%) and gram-positive cocci (6.81%). The most common pathogen was Acinetobacter sp. followed by Klebsiella sp., Candida sp. and Pseudomonas sp. respectively. Among the gram negative organisms, Acinetobacter sp., Klebsiella sp. and Pseudomonas sp. were highly resistant (>80%) to third generation cephalosporins and fluoroquinolones. Resistance to aminoglycosides (>68%) and imipenem (>60%) was also high. Resistance of Pseudomonas sp. to piperacillin-tazobactum was lower (18.2%) in comparison to Acinetobacter sp. and Klebsiella sp. All the Gram-negative organisms were 100% sensitive to colistin except proteus. Regarding gram-positive cocci,Staphylococcus aureus is 100% sensitive to netilmycin and vancomycin with variable resistance pattern to other antibiotics.Conclusion: Emergence of drug resistance against the microorganism causing VAP is a serious concern in most of the ICUs. A knowledge of antibiotic susceptibility pattern will avoid its irrational use in order to control the spread of infection and for proper management of VAP.Bangladesh Crit Care J September 2016; 4 (2): 69-73